Implementasi Media Pembelajaran Interaktif dalam Pembelajaran Pendidikan Agama Islam dan Budi Pekerti di Sekolah Menengah Kejuruan - Muhammad Abrar Parinduri; Ismail Ismail (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2025)
This study analyzes the implementation of interactive learning media in Islamic Religious Education (PAI) and Character Education in vocational high schools within the Merdeka Curriculum framework. Using a qualitative phenomenological approach, this study explores how teachers design, utilize, and evaluate interactive multimedia and artificial intelligence-assisted presentation tools to improve student engagement and learning outcomes. Data were obtained through classroom observations, in-depth interviews with teachers and students, and document analysis of teaching modules and digital materials. Findings indicate that the integration of an AI-based design platform, multimedia presentations, embedded videos, hyperlinks, and digital modules significantly improved students' cognitive engagement, motivation, and conceptual understanding, particularly in abstract and historical materials. Interactive features encourage active participation, collaboration, critical thinking, and communication skills, thus shifting learning practices from teacher-centered to student-centered. This implementation also aligns with the Technological Pedagogical Content Knowledge (TPACK) framework, which emphasizes that effective technology integration requires synergy between content mastery, pedagogical strategies, and digital competencies that are adaptive to learner characteristics. However, this study identified challenges in the form of variations in teachers' digital competencies, limitations in technological infrastructure, and the need for continuous creativity to maintain student learning interest. Overall, this study confirms that interactive learning media is not merely a technical tool, but a strategic pedagogical instrument that supports differentiated learning, strengthening 21st-century competencies, and meaningful learning experiences in the context of contemporary Islamic education.